A numerical study on the unsteady heat transfer in active regenerator with multi-layer refrigerants of rotary magnetic refrigerator near room temperature. (May 2016) - You, Yonghua; Yu, Shen; Tian, Yuqian; Luo, Xiaobing; Huang, Suyi
Highlights: Multi-layer AMR is numerically studied to improve refrigeration performances. AMR with Gd and Gd0.73 Tb0.27 improves qref, V and COP by ～167% and 57%. qref, V of multi-layer AMR is convex with fluid flowrate and alloy proportion. Maximum qref, V and COP of multi-layer AMR equal 1066.7 kW/m 3 and 9.7 respectively. Abstract: As the temperature span(△T) of a refrigerator with an active magnetic regenerator(AMR) of single magneto-caloric material is limited, in the current investigation, the multi-layer AMR consisting of Gd and Gd0.73 Tb0.27 is studied to improve the refrigeration performance at a larger △T with the numerical method, where the experimental magneto-caloric properties are adopted for a better precision. Effects of Gd0.73 Tb0.27 content (φ) and fluid flowrate (qV ) on refrigeration capacity (qref, V ) and coefficient of performance (COP), together with those of hot and cold reservoir temperatures (Tc and Th ), are investigated. Besides, temperature contours of fluid and solid matrix are presented for discussions. The present study demonstrates that compared with AMR of pure Gd, the multi-layer AMR improves the qref, V and COP by ～167% and 57% at △T = 28K, respectively. Moreover, it is observed that qref, V of multi-layer AMR has a convex variation tendency with φ, and the maximum at Tc of 268K equals 874.7 kW/m 3 . As a contrast, COP has two peaks, and the optimal φ is almost independent of Tc, while it decreases with a rising Th . In addition, current investigation indicates that qref, V takes a lager value at a larger qV, while a smaller qV facilitates a good COP.